Chronic Pain and Physical Therapy in Children with Paralytic Syndromes: are there any changes during lockdown? - Orlova, Natalia; Riga, Olena; Ishchenko, Tatiana; Onikiienko, Оlexander; Omelchenko, Olena; Alenina, Inna; Urivaeva, Marina (ALUNA Publishing House, 2022)
The aim: To evaluate an influence of physical therapy on chronic pain in children with paralytic’s syndrome and to maternal emotional status on lockdown time during the COVID-19 pandemic. Materials and methods: Data from 96 children and their mothers (96 persons) were included in the study. On-site services of physical therapists before the pandemic (2018- 2019) were received by 64 children and by 32 children during quarantine measures due to COVID-19 pandemic (2020). The age of the children ranged from 1 to 6 years, the median age was 3 years and 3 months. Results: We note that there were more boys with paralytic syndromes. Among the leading paralytic syndromes, the most common was spastic tetraparesis. The frequency of children with level III–V motor disorders prevailed. Conclusions: The authors consider that physical rehabilitation in children with paralytic syndromes reduces the incidence of moderate chronic pain and improves the emotional state of parents. But, these changes do not occur during the pandemic.
Keywords: children; physical therapy; chronic pain; COVID-19; paralytic syndrome